2006
DOI: 10.1002/ana.21037
|View full text |Cite
|
Sign up to set email alerts
|

Unusually mild tuberous sclerosis phenotype is associated withTSC2R905Q mutation

Abstract: Codon 905 missense mutations in TSC2 are relatively common. The TSC2 R905Q mutation is associated with unusually mild disease, consistent with functional studies. Combined with previous reports, it is apparent that certain TSC2 missense mutations are associated with a mild form of tuberous sclerosis, which in many patients does not meet standard diagnostic criteria. These findings have implications for the large number of patients with limited clinical features of TSC and for genetic counseling in these famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 47 publications
6
60
1
1
Order By: Relevance
“…TSC2 patients with proximal PT mutations and HID mutations showed very similar, significantly lower mean IQ/DQs compared with patients with small, in-frame deletions or missense mutations, confirming case reports finding a milder phenotype in patients with missense mutations. 20,22,[29][30][31] This apparent phenotypic dichotomy corresponds with the reported bimodal IQ/DQ distribution in the TSC2 population and we showed that this bimodal appearance can, at least partly, be explained by the effects of different mutation subtypes. Furthermore, these findings correlate well with functional considerations of the effects of different mutations on the TSC1-TSC2 protein complex.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TSC2 patients with proximal PT mutations and HID mutations showed very similar, significantly lower mean IQ/DQs compared with patients with small, in-frame deletions or missense mutations, confirming case reports finding a milder phenotype in patients with missense mutations. 20,22,[29][30][31] This apparent phenotypic dichotomy corresponds with the reported bimodal IQ/DQ distribution in the TSC2 population and we showed that this bimodal appearance can, at least partly, be explained by the effects of different mutation subtypes. Furthermore, these findings correlate well with functional considerations of the effects of different mutations on the TSC1-TSC2 protein complex.…”
Section: Discussionsupporting
confidence: 89%
“…Thus far, no associations have been found between specific TSC mutation types and cognitive outcomes, 10,19 although there are reports on associations with epilepsy and psychiatric features. 10, [19][20][21][22] As most of these studies have limited power or do not address all mutation types of interest, more extensive investigations are warranted to determine potential correlations between genotype and neurocognitive phenotype in TSC. Furthermore, as mTOR-inhibitors are now under investigation to prevent or reverse neurocognitive morbidity in TSC, more specific information on genotype-phenotype associations will assist clinicians and caregivers in these important treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used immunoblotting, double-label immunofluorescent microscopy, in-cell Western analysis, and GAP assays to study the effects of 47 TSC2 missense and in-frame insertions/deletions and 26 TSC1 missense and inframe insertions/deletions on TSC1-TSC2 activity [Coevoets et al, 2009;Jansen et al, 2006Jansen et al, , 2008Mozaffari et al, 2009;Nellist et al, 2005Nellist et al, , 2008Nellist et al, , 2009. Pathogenic missense changes in the N-terminal region of TSC1 (amino acids 50-224) reduced TSC1 stability [Mozaffari et al, 2009;Nellist et al, 2009], while pathogenic TSC2 missense changes had distinct effects on the TSC1-TSC2 complex, depending on the region of TSC2 that was affected.…”
Section: Introductionmentioning
confidence: 99%
“…TSC2 missense mutations with apparently mild phenotypic effects have been described previously, 23 -25 and have been shown to affect TSC1 -TSC2 function in vitro. 24,25 In the family shown in Figure 6, it seems most likely that the deletion of exons 1 -8 at the TSC2 locus caused TSC in the fetus. We could not rule out the possibility that the TSC2 R98W substitution modifies the phenotype in this family.…”
Section: Immunoblot Analysis Of the Tsc2 Variantsmentioning
confidence: 99%